Entrepreneurial Psychology and Competencies: Some Perspectives from E-Commerce Entrepreneurs in Malaysia - Fadzil, Ahmad Firdause Md; Hashim, Ummi Junaidda; Yaacob, Mohd Rafi; Sallehudin, Hasimi; Muhayiddin, Mohd Nazri; Mukhtar, Dzulkifli; Ibrahim, Rashidah Mohamad (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2 (2019), 2019)
Over the past three decades, studies on entrepreneurship reveal its main components, particularly for new venture creation processes and have been widely discussed by the researchers. An entrepreneur is the main actor in entrepreneurship who is responsible for a new ventures creation. Most of the previous researchers had studied aspects of entrepreneurial cognitive and motivation have approached the process of new ventures creation in general, but overlooked on the e-commerce ventures. The past studies paid the least focus on entrepreneurial competencies which lead to e-commerce new venture creations. In order to fill the lacunae, this study aims to identify the role of cognitive, motivation and competencies that contribute to the creation of new e-commerce ventures in Malaysia. The case study approach was used by interviewing a total of 12 e-commerce entrepreneurs from May 2013 until December 2014. The findings revealed that personal background, work and business skills are among the important factors in the creation of new e-commerce ventures in Malaysia. As entrepreneurs are motivated internally and externally, findings from this study identified 2 types of entrepreneurial motivation which are related to internal motivation; (i) need for achievement and (ii) interest. On the other hand, external motivation as a result of interactions with conducive environment such as customers, family members and industries have increased entrepreneur’s motivation that gives impact to business success. Research findings also have found that entrepreneurial competencies in both computer and communication skills are largely contribute to the creation of new e-commerce ventures. Hence, the government plays an important role in entrepreneurial activities through the encouragement of entrepreneurs’ cognitive ability, motivation, and improve their entrepreneurial competencies. It is certainly that entrepreneurship is among the vital business market that boosts the economic development of the country through the emergence of new ventures in the future. Research paper Keywords: Entrepreneurship; New Venture Creation; Psychology; Competencies; E-Commerce Reference to this paper should be made as follows: Fadzil, A. F. M., Hashim, U. J., Yaacob, M. R., Sallehudin, H., Muhayiddin, M. N., Mukhtar, D., Salleh, F., & Mohamad Ibrahim, R. (2019). Entrepreneurial Psychology and Competencies: Some Perspectives from E-Commerce Entrepreneurs in Malaysia, Journal of Entrepreneurship, Business and Economics , 7 (2), 31–79